Do the Benefits of Male Circumcision Outweigh the Risks? A Critique of the Proposed CDC Guidelines - Earp, Brian D. (Frontiers in Pediatrics, 2015)
The Centers for Disease Control and Prevention (CDC) have announced a set of provisional guidelines concerning male circumcision, in which they suggest that the benefits of the surgery outweigh the risks. In this perspective article, I highlight a few of the key scientific and ethical issues worth considering in interpreting the new CDC recommendations.